Synthesis and characterization of epoxidised jatropha oil for bio-epoxy resins - Ab. Latif, Farah Ezzah (2017)
Synthetic resin has been used in various applications such as an adhesive and in laminating, coating, and painting. Despite its wide applications, its usage raises issues for health, environmental and safety concerns. The synthetisation of bio-resin from renewable resources will be able to introduce compostable and biodegradable plastics which can directly solve many issues such as the floating of the non-biodegradable plastics in the oceans and health concerns of the usage of bisphenol-A. Studies have shown that bio-resin can be used as a bio-reinforcement in a composite formulation. However, there is no research done to produce a hybrid bio-matrix for composite application by improving its formulation of blended synthetic resin with bio-resin. Thus, this study would like to introduce the optimisation and characterisation of the epoxidation reaction of Malaysian crude jatropha oil with the presence of ion exchange resin as well as the mechanical properties of the hybrid bio-matrix. The study found that the optimum epoxidised crude jatropha oil (ECJO) was achieved by reacting 1 mol (263.16 g) of crude Jatropha oil with 0.6 molar ratio of glacial acetic acid, 1.7 molar ratio of 30% hydrogen peroxide, and 16 wt. % of ion exchange resins. The optimal epoxidation process was carried out at a temperature of 60 °C for 5 hours. The epoxidation process was accomplished by obtaining a high oxirane content (OOC) of 3.71%. The formation of oxirane ring was confirmed by FTIR, 13CNMR, and 1HNMR at 822 cm-1, 54.203-57.26 ppm, and 2.809-3.031 ppm respectively. The activation energy (Ea), average activation enthalpy (ΔH), and average activation Gibbs free energy (ΔG) of the epoxidation process were found to be 35.91 kJ/mol, 33.16 kJ/mol, and 117.21 kJ/mol respectively. The hybrid bio-matrix with the blend of 25-75% of the ECJO\Epoxamite 103 was found to be relatively rigid and brittle with the tensile strength and modulus as well as flexural strength and modulus of 30.29±4.43 MPa, 464.46±137.10 MPa, 47.44±2.57 MPa, and 1568.59±60.61 MPa respectively. Thus, it is recommended to use 10-25% of the epoxy bio-resin in blends with the standard commercial epoxy resins as an optimal replacement for the synthetic petro-based products.